Foreign policy theories, actors, cases - Smith, S. A. (Stephen Anthony) 1952-; Hadfield-Amkahn, Amelia; Dunne, Tim (Timothy) 1965- (Oxford University Press, 2016)
This ground breaking text provides the ideal introduction to the ever-changing field of foreign policy. With a unique combination of theories, actors and cases in a single volume, the expert contributors provide students with a valuable and accessible introduction to what foreign policy is and how it is conducted. With an emphasis throughout on grounding theory in empirical examples, the textbook features a section dedicated to relevant and topical case studies where foreign policy analysis approaches and theories are applied. The expert team of contributors clearly conveys the connection between international relations theory, political science, and the development of foreign policy analysis, emphasizing the key debates in the academic community.